The Impact of Nurse Experience and Sequential Organ Failure Assessment on Nurses' Workflow in an Intensive Care Unit. (December 2020) - Kasaie, Alireza; Hyup Kim, Jung; Guo, Wenbin; Despins, Laurel
The purpose of this study is to understand the impact of Nurse Experience (NE) and Sequential Organ Failure Assessment (SOFA) on nurses' workflow and process time in an Intensive Care Unit (ICU). In this study, a combination of data from the time-motion study observations, ICU nurses' Real-Time Location System (RTLS), and the Real-Time Measurement System (RTMS) data were used to develop multiple Hierarchical Task Analysis (HTA) charts. HTA chart helped us to identify the ICU nurses' workflow patterns. The results showed that ICU nurses spent over 47% of their time on performing primary care (in-room activities) and 25% on out-of-room activities. Furthermore, NE levels and SOFA scores had significant impacts on the average process time of nurse handoff, in-room Electronic Medical Record (EMR) charting, and the workflow patterns of out-of-room activities and out-of-room EMR usage. The outcomes of this study will provide a detailed workflow of ICU nurses and might help nurse managers to conduct a better strategy for improving ICU nurse's workflow.